Low Current Densities Toggle Optical Polarization Switching in Pt/Yttrium Iron Garnet Magnetic Heterostructures Using Energy Resolution. Issue 9 (10th July 2020) - Chien, Wan-Hsiu Chang; Huang, Jing-Ya; Lin, Jun-Xiao; Liao, Yen-Fa; Su, Hung-Wen; Liang, Hsia-Ling; Huang, Ssu-Yen; Yao, Yeong-Der; Hsu, Hua-Shu
Abstract : Spin current, which is converted from the charge current in heavy metals, is widely used to manipulate magnetization in heavy metal/magnetic insulator systems. However, there is scant research on how the spin‐polarized density of states (DOS) is affected by the absorption of spin current. This study investigates the spin‐current‐induced magnetic variation of an yttrium iron garnet (YIG) ﬁlm driven by charge current in an overlayer of Pt that uses energy‐resolved magnetic circular dichroism (MCD) spectra as an example. MCD intensity can be manipulated reversibly using an applied current at near d–d transitions. Furthermore, the MCD sign, which is associated with an elliptically polarized direction, is reversed by a relatively low current density (≈10 8 A m −2 ) near YIG charge transfer transitions, even without the assistance of a magnetic field. The spin accumulation in Fe orbits and the corresponding change in spin‐polarized DOS explain the observed phenomenon. This paves the way to low‐dissipation spintronics and electrically controlled magneto‐optical devices based on magnetic insulators. Abstract : Due to the intrinsic character of yttrium iron garnet (YIG) spin‐polarized band structure measured by energy‐resolved magnetic circular dichroism, the spin accumulation resulting from the spin current generated from Pt leads to low current densities (≈10 8 A m −2 ) control and switching optical polarization of YIG by selecting excited energies near d–d transitions and charge transfer transition, respectively.